Balloon Eustachian tuboplasty: a retrospective cohort study. (December 2015) - Schröder, S.; Lehmann, M.; Ebmeyer, J.; Upile, T.; Sudhoff, H.
Abstract : Background: Eustachian tube dysfunction is regarded as a 'black box' term, reflecting a spectrum of dysfunction. The key to its diagnosis and management is in identifying the aetiology and exact pathophysiology of the dysfunction. Design: We present our retrospective 5‐year results for the technique of transnasal endoscopic balloon dilatation of the cartilaginous part of the Eustachian tube, balloon Eustachian tuboplasty (BET). The indication for treatment is chronic obstructive Eustachian tube dysfunction. Main outcome measures: Preoperatively, the Eustachian tube score (ETS) was obtained by a clinico‐objective assessment involving tubomanometry (TMM) and reported patient symptom. The measurements were repeated 1, 2, 3, 4 and 5 years postoperatively. Setting: Tertiary referral centre. Participants: A total of 622 patients (1076 ears) were treated with BET. Results: One year after treatment, the Eustachian tube score improved from 3.13 (± 2.47 SD) to 5.75 (± 2.76 SD). The Eustachian tube score improved significantly in 73% of ears. The average Eustachian tube score 2 years after treatment improved from 2.65 (± 2.89 SD) to 6.26 (± 3.07 SD). In 82% of patients, the Eustachian tube score improved significantly at 5 years. The subjective satisfaction of the patients was approximately 80%. Conclusions: Our long‐term results suggest that BET is a safe and feasible treatment for chronic obstructive Eustachian tube dysfunction with a success rate of more than 70%. This study has important implications for other Eustachian tube‐related clinical entities, such as glue ear management (adults and children), continued grommet insertion and tympanomastoid surgery outcomes.